Reactivity of a Silsesquioxane Organofunctionalized with 4-Amino-5-Phenyl-4H-[1,2,4]-Triazole-3-thiol: Complementary Characterization and an Application to Chronoamperometric Detection of L-Dopamine - Fernandes, Daniela Silvestrini [UNESP]; Maraldi, Vitor Alexandre [UNESP]; Filho, Newton Luiz Dias [UNESP]; Do Carmo, Devaney R. [UNESP] (Springer Nature, 2018)
This work describes the organofunctionalization and a complementary characterization and application of an octakis(3-chloropropyl)octasilsesquioxane (1) with 4-Amino-5-Phenyl-4H-[1,2,4]-Triazole-3-Thiol (2). The functionalized silsesquioxane (3) was characterized by nuclear magnetic resonance, X-ray diffraction, transmission electron microscopy and thermogravimetric analysis. After functionalized, the silsesquioxane can interact with copper chloride and subsequently with potassium hexacyanoferrate (III) (4). The hybrid composite formed (4) was characterized by FT-IR and diffuse reflectance. The compound 4 included into a work graphite paste electrode (20% w/w) was examined for chronoamperometric determination of L-Dopamine. The modified graphite paste electrode with compound 4 showed a linear response from 2.5× 10− 5 at 4.0× 10− 4 mol L− 1. The modified graphite paste electrode with 4 showed a detection limit of 2.08× 10− 4 mol L− 1 with a relative standard deviation of ± 2% (n = 3) and amperometric sensitivity of 0.136 A mol L− 1.
Keywords: Characterization; Chronoamperometry; L-Dopamine; Silsesquioxanes; Synthesis; Triazole